7-2х=9х-8х-8
-2х-9х+8х= -8-7
-3х= -15
х= -15:(-3)
х=5
Ответ:
при х = 5
Пошаговое объяснение:
7 - 2x = 9x -8(x + 1)
7 - 2х = 9х - 8х - 8
-2х - 9х + 8х = -7 - 8
-3х = -15
х = -15/-3
х = 5
-----------
Проверим:
7 - 2*5 = 9*5 -8(5 + 1)
7 - 10 = 45 - 8*6
-3 = 45 - 48
-3 = -3 - верно
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
7-2х=9х-8х-8
-2х-9х+8х= -8-7
-3х= -15
х= -15:(-3)
х=5
Ответ:
при х = 5
Пошаговое объяснение:
7 - 2x = 9x -8(x + 1)
7 - 2х = 9х - 8х - 8
-2х - 9х + 8х = -7 - 8
-3х = -15
х = -15/-3
х = 5
-----------
Проверим:
7 - 2*5 = 9*5 -8(5 + 1)
7 - 10 = 45 - 8*6
-3 = 45 - 48
-3 = -3 - верно